Comparative effectiveness of ciltacabtagene autoleucel in CARTITUDE‐1 versus physician's choice of therapy in the Flatiron Health multiple myeloma cohort registry for the treatment of patients with relapsed or refractory multiple myeloma. Issue 1 (10th December 2021) - Martin, Thomas; Krishnan, Amrita; Yong, Kwee; Weisel, Katja; Mehra, Maneesha; Nair, Sandhya; Qi, Keqin; Londhe, Anil; Diels, Joris; Crivera, Concetta; Jackson, Carolyn C.; Olyslager, Yunsi; et al.
Abstract: Introduction: Ciltacabtagene autoleucel (cilta‐cel) is a novel chimeric antigen receptor T‐cell therapy that is being evaluated in the CARTITUDE‐1 trial (NCT03548207) in patients with relapsed or refractory multiple myeloma (RRMM) who received as part of their previous therapy an immunomodulatory drug, proteasome inhibitor, and an anti‐CD38 monoclonal antibody (i.e., triple‐class exposed). Given the absence of a control arm in CARTITUDE‐1, this study assessed the comparative effectiveness of cilta‐cel and physician's choice of treatment (PCT) using an external real‐world control arm from the Flatiron Health multiple myeloma cohort registry. Methods: Given the availability of individual patient data for cilta‐cel from CARTITUDE‐1 and PCT in Flatiron, inverse probability of treatment weighting was used to adjust for unbalanced baseline covariates of prognostic significance: refractory status, cytogenetic profile, International Staging System stage, time to progression on last regimen, number of prior lines of therapy, years since diagnosis, and age. Comparative effectiveness was estimated for progression‐free survival (PFS), time to next treatment (TTNT), and overall survival (OS). A range of sensitivity analyses were conducted. Results: Baseline characteristics were similar between the two cohorts after propensity score weighting. Patients with cilta‐cel had improved PFS (HR: 0.18 [95% CI: 0.12, 0.27; p  < 0.0001]), TTNT (HR: 0.15 [95% CI: 0.09, 0.22; p  < 0.0001]), and OS (HR: 0.25 [95% CI: 0.13, 0.46; p  < 0.0001]) versus PCT. Cilta‐cel treatment benefit was robust and consistent across all sensitivity analyses. Conclusion: Cilta‐cel demonstrated significantly superior effectiveness over PCT for all outcomes, highlighting its potential as an effective therapy in patients with triple‐class exposed RRMM.